2016
DOI: 10.1177/1077546315585038
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive Elman neural network with C-PSO learning algorithm based pitch angle controller for DFIG based WECS

Abstract: Frequent variation in the wind flow affects the Wind Turbine (WT) to generate fluctuating output power and this can negatively impact the entire power network. This paper aims at modelling an Enhanced-Elman Neural Network (EENN) based pitch angle controller to mitigate the output power fluctuation in a grid connected Wind Energy Conversion System. The outstanding aspect of the proposed controller is that, they can smoothen the output power fluctuation, when the wind speed is above or below rated speed of the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(20 citation statements)
references
References 29 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…Though, by analysing the alteration principle of the wind power, it is found that combined pitch and power management controller can regulate the produced wind power by regulating the angular rotational speed of the WT to optimum value. [14][15][16][17][18][19][20] The equilibrium between the power production and power consumption of the load is achieved when the total power generated by WPGS is equal to the total load demand in addition to the power losses. The prediction of the wind speed all around year in particular site area could be easier to estimate the obtainable wind power from the wind farm and that could satisfy the load power constraints.…”
Section: Power Management Using the Proposed Strategymentioning
confidence: 99%
See 3 more Smart Citations
“…Though, by analysing the alteration principle of the wind power, it is found that combined pitch and power management controller can regulate the produced wind power by regulating the angular rotational speed of the WT to optimum value. [14][15][16][17][18][19][20] The equilibrium between the power production and power consumption of the load is achieved when the total power generated by WPGS is equal to the total load demand in addition to the power losses. The prediction of the wind speed all around year in particular site area could be easier to estimate the obtainable wind power from the wind farm and that could satisfy the load power constraints.…”
Section: Power Management Using the Proposed Strategymentioning
confidence: 99%
“…The coupled shaft is modelled as a spring and a damper. The equation for the shaft system is given as 17…”
Section: Investigated System Modelling and Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [4] a non-dominated sorting GA alongside discrete Fourier transform is implemented to quantify the damping characteristics of the rotor-side current due to system disturbance. In recent years, different evolution algorithms [5], [6] including mean variance optimization (MVO) algorithm [7], GA [8], PSO [9][10][11][12], bacteria foraging optimization (PFO) algorithm [13], hybrid artificial neural network [14] and Gbest guided artificial bee colony algorithm [15], [16] are applied to optimize the parameters of the PI controller of the rotor side converter (RSC) and hence improve the damping of oscillatory modes in DFIG-based WECS. In [17] a PSO is presented to generate an on-off controller to ensure robustness and quality of the energy produced, wherein [18] a nonlinear rotor-side controller is designed based on H 2 optimal control theory to demonstrate the synthesis of a maximum power point tracking (MPPT) algorithm.…”
Section: Introductionmentioning
confidence: 99%